A comparison of different nonlinear shell theories for rotating fluid‐filled structures. Issue 1 (24th March 2023) - Schmidt, Rico; Ams, Alfons
Abstract: Rotating fluid‐filled shell structures can be used for different applications in technique. Because of spin‐softening as well as stress‐stiffening it is essential to consider geometrical non‐linearities. Additionally, shear deformation is getting important in case of thick shells. At this point different theories from KIRCHHOFF‐LOVE (no shear deformation) and MINDLIN‐REISSNER (first order shear deformation) are compared with each other. For both theories the nonlinear kinematics are shown and therewith the HAMILTON's principle is evaluated to receive the equations of motion. The solution of the corresponding eigenvalue problem is done with a global RITZ approach on the one hand, on the other hand with local FE‐discretization. Different results of rotating and non‐rotating cylindrical shells with respect to their eigenfrequencies are presented and compared. Furthermore, experimental data is used for validation.